Pelatihan Pembuatan Sabun Dari Minyak Jelantah Sebagai Upaya Peningkatan Kepedulian Masyarakat Terhadap Lingkungan - Lisa Ratnasari; Bernard Hasibuan; Ninin Gusdini (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Pangandaran Beach is one of the famous tourist destinations in West Java. The people around the tourist site of Pangandaran beach are many wholike the restaurant business. The waste produced includes leech oil which is the remaining oil produced by frying. The resulting waste oil is never utilized further, just thrown into the environment. With a large number of restaurants, the waste cooking oil produced is also a lot.  To overcome this problem, it is necessary to carry out activities aimed at increasing the added value of cooking oil waste by processingit into soap. From the training program that has been implemented, participants are very appreciative and amazed by the results of making soap from leech oil. This activity also has a positive impact with the opening of business opportunities for processing oil into soap so that it has an impact on increasing economic income for culinary traders. In addition, reducing the disposal of waste oil, thus maintaining the preservation of the environment and health.